PENGARUH MINAT BELAJAR DAN KEPERCAYAAN DIRI TERHADAP HASIL BELAJAR MATEMATIKA - Salmawati Salmawati (JURNAL ILMIAH NUSANTARA, 2025)
This study aims to determine the influence of learning interest and confidence on the mathematics learning outcomes of grade VIII students of SMP Negeri 1 Anggaberi. This type of research is Ex-post facto using a quantitative approach. The population in this study is 47 students. In this study, a sample of 32 students from 47 students in grade VIII of SMP Negeri 1 Anggaberi was used. The data collection technique in this study uses (1) a learning interest questionnaire, (2) a confidence questionnaire, and (3) documentation of students' mathematics learning outcomes. The data analysis technique in this study consists of two, namely descriptive and inferential. The results of the descriptive analysis showed that the learning interest of grade VIII students of SMP Negeri 1 Anggaberi was in the medium category with a percentage of 65%, while the confidence of grade VIII students of SMP Negeri 1 Anggaberi was in the medium category with a percentage of 66%, and for the mathematics learning outcomes of grade VIII students of SMP Negeri 1 Anggaberi is in the sufficient category with a percentage of 72%. The results of inferential analysis were obtained, partially learning interest showed a significant influence on students' mathematics learning outcomes, shown by the value of tcal = 2.51 > ttable(0.05; 30) = 2.04, while self-confidence has no effect on students' mathematics learning outcomes, where the value of tcount = 0.69 < ttable = 2.04, and simultaneously the value of Fcal = 9.83 > Ftable = 3.33, then H0 is rejected and H1 is accepted, then it can be concluded that together learning interest and confidence have a significant effect on the mathematics learning outcomes of grade VIII students of SMP Negeri 1 Anggaberi with a large contribution of 40.4%. This means that the contribution of independent variables to dependent variables is 40.4%.